Measurement uncertainty evaluation of the wind speed in the atmospheric boundary layer - Kartashov, Volodymyr; Shapovalov, Serhii (Видавництво Львівської політехніки, 2024)
A method for measuring wind speed by the trajectory of an acoustic package under the influence of air flows in the boundary atmospheric layer is developed. Model equations for measurement components of wind speed evaluation are ob- tained. For each of the components, an equation for the combined standard uncertainty is written, sensitivity coefficients are calcu- lated for input quantities, and uncertainty budgets are constructed. The last can serve as the basis for creating a software tool for measurement uncertainty evaluation.
Keywords: wind speed; boundary atmospheric layer; model equation; measurement; uncertainty budget